Cultura di corte nel secolo XVIII spagnolo e italiano: diplomazia, musica, letteratura e arte, I, Politica e diplomazia - Guasti, Niccolò; Rao, Anna Maria (Clio. Essays in History, Archaeology and Art History, 2023)
The volume collects the contributions of international scholars on court culture in Spain and in the Italian states in the eighteenth century, presented on the occasion of the second international congress of the Italian society and the Spanish society of studies on the eighteenth century, held in Salamanca on 16- March 18, 2022. Particular attention is paid to the political and diplomatic aspects, investigated through a wide range of different sources: public and private correspondence, memoirs, ceremonies, iconographic sources. The royal and noble courts are flanked by the papal court and the many courts animated by ministers, patricians, nobles and noblewomen, and by the diplomatic agents themselves. The study of political and cultural exchanges between their various courtly locations is intertwined with the comparative investigation between Italy and Spain. What emerges is an unprecedented picture of the relations between the Italian states and the Spanish monarchy in the eighteenth century.